Media Pembelajaran Audio Visual Berbasis Video Scribe Pada Materi Pengurangan Pecahan Kelas V Sekolah Dasar - Pratiwi, Komang Ayu Martha Arista; Suarjana, I Made; Ujianti, Putu Rahayu (Universitas Pendidikan Ganesha, 2025)
Mathematics education is regarded as a key to unlocking promising career opportunities for students and preparing them to compete in the field of technology; however, the expected innovative learning process has not been fully realized. One contributing factor is the lack of appropriate, engaging, and interactive learning media to help students understand the topic of fraction subtraction. This gap has resulted in low student interest and comprehension regarding the material. This study aimed to design and develop an audiovisual learning medium using VideoScribe for fifth-grade elementary students, and then evaluate the validity of the developed media. The research employed the 4D model (Define, Design, Develop, Disseminate), with data collected through questionnaires. Validation involved subject matter experts, media experts, and education practitioners. Data were analyzed using descriptive qualitative and quantitative methods with a five-point scale. The validation results indicated average scores of 4.5 (subject expert), 4.66 (media expert), and 4.86 (practitioner), demonstrating that the media is valid and feasible. The media follows a systematic structure, adopts a concrete-to-abstract approach, and integrates character values aligned with the Merdeka Curriculum. Further development is recommended, including interactive features, field trials, and application to additional mathematics topics.